Babao Dan decreases hepatocarcinogenesis by inhibiting hepatic progenitor cells malignant transformation via down-regulating toll-like receptor 4 - Liang, Lei; Zhang, Lu-Yao; Liu, Wen-Ting; Zong, Chen; Gao, Lu; Li, Rong; Zhao, Qiu-Dong; Zhao, Na-Ping; Wei, Li-Xin; Zhang, Li; Han, Zhi-Peng (Frontiers in Oncology, 2023)
Background Babao Dan (BBD) is a traditional Chinese medicine that has been widely used as a complementary and alternative medicine to treat chronic liver diseases. In this study, we aimed to observe the effect of BBD on the incidence of diethylnitrosamine (DEN)-initiated hepatocellular carcinoma formation in rats and explored its possible mechanism. Methods To verify this hypothesis, BBD was administrated to rats at a dose of 0.5g/kg body weight per two days from the 9th to 12th week in HCC-induced by DEN. Liver injury biomarkers and hepatic inflammatory parameters were evaluated by histopathology as well as serum and hepatic content analysis. We applied immunohistochemical analysis to investigate the expression of CK-19 and SOX-9 in liver tissues. The expression of TLR4 was determined by immunohistochemical, RT-PCR, and western blot analysis. Furthermore, we also detected the efficacy of BBD against primary HPCs neoplastic transformation induced by LPS. Results We observed that DEN could induce hepatocarcinogenesis, and BBD could obviously decrease the incidence. The biochemical and histopathological examination results confirmed that BBD could protect against liver injury and decrease inflammatory infiltration. Immunohistochemistry staining results showed that BBD could effectively inhibit the ductal reaction and the expression of TLR4. The results showed that BBD-serumcould obviously inhibit primary HPCs neoplastic transformation induced by regulating the TLR4/Ras/ERK signaling pathway. Conclusion In summary, our results indicate that BBD has potential applications in the prevention and treatment of HCC, which may be related to its effect on hepatic progenitor cells malignant transformation via inhibiting the TLR4/Ras/ERK signaling pathway.